Peran Modal Sosial dalam Memperkuat Jaringan Kelompok Tani Hutan di Kampung Kapitan Kecamatan Belinyu Kabupaten Bangka: The Role of Social Capital in Strengthening Forest Farmer Group Networks in Kapitan Village, Belinyu Sub-district, Bangka Regency - Herdiyanti Herdiyanti; Sarpin Sarpin; Bustami Rahman; Citra Asmara Indra (Society, 2022)
This research focuses on a village in Belinyu Sub-district, Bangka Regency, Kapitan Village. This research uses descriptive qualitative methods and a literature review with observation and documentation data collection techniques. The study’s results found that social capital plays an important role in strengthening the network of the Forest Farmers Groups, where one of the efforts is the Karang Lintang Festival. The community in Kampung Kapitan has been built with a social capital system based on trust, norms, and network relationships. This festival activity is one of the efforts to encourage participation and increase community social capital through bonding, bridging, and linking social relationships. The theory used in this research is Woolcock’s social capital theory. As stated by Woolcock, the types of social capital become this research’s reference to analyze the role of social capital in the community. The strength of this network is obtained through wide-scale or national relationships that the Forest Farmers Group has achieved with government agencies. Of course, strengthening the network of this group is accompanied by an increase in tourism potential in Kapitan Village.